Perspektif Hukum Islam Pada Akad Jual Beli Properti di Kota Kendari: Studi Kasus Properti Fatihah Residence Kendari - Arif Agung Winarto (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
This study aims to determine the implementation of cash and credit buying and selling agreements in the law of buying and selling houses at Fatihah Residence in the perspective of Islamic law. The data used in this study were primary data obtained from interviews with informants. This research uses a qualitative approach with informants of the Chairman / director (HRD), Staff of the marketing department, Staff of the legal section of the contract, Notarial deed officials, Customers or consumers who are within the scope of the Fatihah Residence Property kendari which is selected by purposive sampling. The results of this study are a sale and purchase card with an Istisnah contract and a Murabahah contract in the perspective of Islamic law at Fatiha Residence Kendari Property which provides relief for consumers in the form of flat installments and is not subject to fines when there is a delay in installment payments.